Refleksi dan Penguatan Karakter Entrepreneur Muslim dalam Dinamika Ekonomi Global - Moh. Ainul Yaqin; Akun Fariha Imaroh; Muhammad Sidiq Purnomo (BAMALA Institute, 2026)
The dynamics of the global economy in the third decade of the twenty-first century require a reorientation of the entrepreneurial paradigm that integrates material profitability with moral and spiritual sustainability. This article aims to explore reflections and strategies for strengthening the character of Muslim entrepreneurs as an antithesis to the moral crisis in modern business. Employing a qualitative approach with a library research method, this study analyzes authoritative literature on Islamic business ethics, prophetic leadership, and Maqasid al-Shari'ah. The findings indicate that the internalization of the Tawhid paradigm transforms the vision of business into an act of worship and a manifestation of humanity's role as khalifah fil ardh (vicegerent on earth). Character strengthening is achieved through the implementation of the four prophetic traits Siddiq (truthfulness), Amanah (trustworthiness), Tabligh (effective communication), and Fathonah (wisdom and intelligence) which are adapted to the context of Industry 5.0, including ethical data integrity and innovation. Furthermore, the concepts of Digital Taqwa and Islamic Work Ethics (IWE) are identified as effective internal control mechanisms through the cultivation of Muraqabah (God-consciousness). This study concludes that strengthening the character of Muslim entrepreneurs through the integrated approaches of education, habituation, and regulation will develop valuable social capital to realize the vision of Rahmatan lil 'Alamin (mercy to all creation) within a just and sustainable global economic ecosystem.